Applying Consumer Safety Principles in Fast-Food Restaurant Food Production Processes - Revania Fedira,; Muthia Sakti, (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
The increasing public interest in fast food restaurants demands the implementation of food safety standards to protect consumers. This study examines the application of consumer security and safety principles in food production processes at fast food restaurants and the role of the Health Department. This study utilizes normative juridical methods complemented by a statutory approach and data sources through literature studies and interviews with the DKI Jakarta Provincial Health Office, which is responsible for guidance and supervision of ready-to-eat processed foods. The findings show that Indonesian legal regulations have adequately regulated the standardization of food production processes by applying consumer security and safety principles. The Health Office plays an active role in maintaining consistent application of these principles through guidance programs, including Ready-to-Eat Food Safety Training and educational material dissemination, as well as supervision through Environmental Health Inspections and mandatory Hygiene Sanitation Eligibility Certificates, accompanied by administrative sanctions for businesses violating food safety standards.